Toxicity of definitive and post-operative radiation following ipilimumab in non-small cell lung cancer. (August 2016) - Boyer, Matthew J.; Gu, Lin; Wang, Xiaofei; Kelsey, Chris R.; Yoo, David S.; Onaitis, Mark W.; Dunphy, Frank R.; Crawford, Jeffrey; Ready, Neal E.; Salama, Joseph K.
Highlights: Toxicity of radiation following ipilimumab for NSCLC explored. No grade 3 or greater toxicity with radiation following ipilimumab. Radiation after ipilimumab is feasible as neo-adjuvant treatment for NSCLC. Abstract: To determine the feasibility and toxicity of radiation therapy, delivered either as definitive treatment or following surgery, following neo-adjuvant immune checkpoint inhibition for locally advanced NSCLC sixteen patients who received neo-adjuvant chemotherapy including ipilimumab as part of a phase II study were identified. Patients were analyzed by intent of radiation and toxicity graded based on CTCAE 4.0. There were seven patients identified who received definitive radiation and nine who received post-operative radiation. There was no grade 3 or greater toxicity in the definitive treatment group although one patient stopped treatment early due to back pain secondary to progression outside of the treatment field. In the post-operative treatment group, one patient required a one week break due to grade 2 odynophagia and no grade 3 or greater toxicity was observed. In this study of radiation as definitive or post-operative treatment following neo-adjuvant chemotherapy including ipilimumab for locally advanced NSCLC was feasible and well tolerated with limited toxicity.